Psychosocial effects of the humanoid socially assistive robot Coach Pepper on informal caregivers of people with dementia: A mixed‐methods study. (31st December 2021) - Zuschnegg, Julia; Schüssler, Sandra; Paletta, Lucas; Voithofer, Claudia; Lodron, Gerald; Orgel, Thomas; Russegger, Silvia; Schneeberger, Michael; Fellner, Maria; Steiner, Josef; Pansy‐Resch, Sandra; Holter, Magdalena; et al.
Abstract: Background: Dementia care is largely provided by informal caregivers, which can present significant challenges and increase caregivers' burden. Humanoid socially assistive robots (SARs) have the potential to provide assistance, but evidence is missing. The aim was to explore the psychosocial effects of Coach Pepper (humanoid SAR system "AMIGO" combined with a tablet PC‐based dementia training) versus an exclusive tablet PC‐based dementia training on informal caregivers of people with dementia living at home (as well as their experiences). Method: A randomized controlled trial with a complementary qualitative part was performed (May 2019‐March 2020). 32 informal caregivers of people with dementia living at home participated in the study. The intervention group received Coach Pepper and the control group received only the tablet‐based dementia training. The duration of the intervention was three weeks per household. Data was collected at baseline and after the intervention by standardized questionnaires for caregiver burden (primary outcome), quality of life, depressive symptoms and affect. Additionally, interviews about caregivers' experiences were conducted in the intervention group. Result: Participants were on average 58.2 (±12.5) years old and predominantly female (68.8%). Quality of life, depressive symptoms and affect demonstrated no significant differences regarding between‐group mean changes, neither did caregivers' burden, which showed decreasing tendencies of burden in the intervention and control group (Zarit Burden Interview, ‐2.7±8.7 vs. ‐4.4±6.4, p=0.2552). Qualitative findings revealed that participants had positive attitudes regarding Coach Pepper and experienced it as neutral in terms of burden. Some stated that Coach Pepper provided relief/more free time by entertaining the persons with dementia. However, some participants stated that they had to invest additional time until the person with dementia was able to engage with Coach Pepper and that its usability should be improved in certain areas (e.g., communication) to constitute more support for caregivers. Conclusion: Coach Pepper had no significant psychosocial effects on informal caregivers of people with dementia. Qualitative findings demonstrated the participants' positive attitudes but highlighted a need for improvement regarding its usability. This study contributes to the development/modification of Coach Pepper based on caregivers' needs in dementia care.